THE EFFICIENCY OF USING A SMART GREENHOUSE IN THE OMAD FARM IN THE YANGIBAZAR DISTRICT OF THE KHOREZM REGION (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article describes the methods of using a smart greenhouse in the Omad farm in the Yangibazor district of the Khorezm region, its operation in accordance with the climate and methods for obtaining such a high-quality and abundant harvest.